2002
DOI: 10.1126/science.1068996
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interspecific Variation in Primate Gene Expression Patterns

Abstract: Although humans and their closest evolutionary relatives, the chimpanzees, are 98.7% identical in their genomic DNA sequences, they differ in many morphological, behavioral, and cognitive aspects. The underlying genetic basis of many of these differences may be altered gene expression. We have compared the transcriptome in blood leukocytes, liver, and brain of humans, chimpanzees, orangutans, and macaques using microarrays, as well as protein expression patterns of humans and chimpanzees using two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
611
6
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 779 publications
(661 citation statements)
references
References 10 publications
36
611
6
8
Order By: Relevance
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate, albeit related, explanation would be that regions with low genetic variance have greater functional constraints on their determinants of cortical thickness, such that genetic mutations influencing these regions will typically be eliminated quickly from the population through purifying selection. Comparative genomic experiments have shown that a subset of neurally-expressed genes have evolved more rapidly in humans than in other primates [Chimpanzee Sequencing and Analysis Consortium, 2005;Dorus et al, 2004;Khaitovich et al, 2005]; both gene expression changes and protein sequence modification have accelerated in humans relative to nonhuman primates [Caceres et al, 2003;Enard et al, 2002;Gu and Gu, 2003;Hsieh et al, 2003;Uddin et al, 2004]. The findings of increased genetic variance in evolutionarily recent structures may represent a remnant of these rapid neurogenetic changes that accompanied our divergence from other primates.…”
Section: Discussionmentioning
confidence: 99%
“…By now it is wellrecognized that cis-regulatory change is a key process in evolution for the origin of distinct phenotypes in eukaryotes (Enard et al, 2002). In bacteria, the importance of gene-expression as a governing factor for evolution, habitat adaptation and diversification is recognized as well (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…The aim has been to characterize general trends in the evolution of gene expression rather than to identify specific genes of interest. To date, conclusions about the selection pressures acting on gene expression have been conflicting 2,3,6,[11][12][13] .These studies have all relied on data collected from arrays using gene probes that were designed on the basis of human sequences only. However, sequence mismatches affect hybridization intensity and can therefore bias estimates of gene expression differences between species 14 .…”
mentioning
confidence: 99%